THE WISDOM OF UZBEK PROVERBS INVOLVING SOMATIC UNITS: CULTURAL INSIGHTS AND PRACTICAL LESSONS (Modern education and development, 2024)
This article explores Uzbek proverbs that feature somatic expressions and analyzes how they reflect cultural values and practical wisdom. Proverbs such as, ,,Yelka yelka bilan og'irlikni ko'taradi"  ( "Shoulder to shoulder, one can bear the weight") and ,, Barmoqni qaysi tomonlama bursa og'riydi" ("Whichever way you bend a finger, it will hurt") emphasize the importance of working together to overcome difficulties and highlight the value of each family member or close individual. Through analysis, the article examines the broad application of these proverbs in daily life and their role in preserving cultural values. By gaining a deeper understanding of these proverbs, we can gain insight into the social structure of Uzbekistan and appreciate the enduring relevance of traditional values in modern times.